Amyloid beta precursor protein and ubiquitin epitopes in human and experimental dystrophic axons. Ultrastructural localization. - Bacci, B. (1994)
Dystrophic axons (DA) represent a major pathological feature of several neurodegenerative disorders, including infantile neuroaxonal dystrophy (INAD) and Alzheimer disease. We have previously presented evidence that amyloid beta precursor protein (BPP) and ubiquitin (Ub) are present in DA of different origin. We have now characterized the immunoreactivity of DA experimentally induced in rat by the administration of parabromophenylacetylurea (BPAU) and examined the subcellular localization of Ub and BPP in BPAU-induced DA and in DA present in subjects affected by INAD. BPAU-induced DA strongly immunoreacted with antisera to Ub and to COOH- and NH2-terminal regions of BPP. Immunoblots of DA-enriched brain regions were consistent with an increase in the amount of Ub and BPP in DA. Moreover, BPAU-induced DA immunoreacted with antibodies to PGP 9.5, a neuronal-specific Ub COOH-terminal hydrolase, and to the inducible heat shock protein 70. Antigenic characterization also indicated that the tubulovesicular membranes within DA derived largely from the smooth endoplasmic reticulum rather than from the Golgi system or the synaptic vesicles. Subcellular immunolocalization of Ub and BPP in both INAD- and BPAU-induced DA revealed that Ub and BPP colocalize in granulovesicular material in both conditions. In INAD DA intense Ub immunoreactivity was also detected in nonmembranous electron dense structures that were present only in these DA, probably because of the chronic course of INAD. Although BPP immunostaining may be related to accumulation of BPP-containing membranes in DA, Ub immunostaining is likely to result from activation of the Ub system by the neuron in the attempt to remove excessive and possibly abnormal proteins. A similar pathogenesis can be postulated for DA of Alzheimer disease.